Multiple Responses Analysis using SPSS (Dichotomies Method): A Beginner’s Guide - Donald, Stephen (2016)
A guide for performing Multiple Responses Analysis using SPSS. Multiple response refers to the situation when participants are allowed to select more than one option for a question.